Beans - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1979)
The status of CIAT bean technology development is analyzed and technology transfer activities in the crop in Latin America are indicated. Each phase in the development of technology that will allow major bean yield increases is discussed, namely the identification of production constraints, germplasm collection and evaluation, cv. improvement using wild or landrace cv., development of improved cultural practices, transfer of materials to national programs, and on-farm testing. Although the yield gains to date are low compared with those obtained in other crops, progress has been made. Also, germplasm moves freely in Latin America. The disease problems identified can be overcome and many of the resistance breeding problems are less difficult than 1st anticipated. High yields, initially available in black cv., are now attained with other seed coat colors, and a wide range of materials are used by national programs. Specific collaborative projects of technology transfer are carried out in Mexico, Guatemala, Honduras, El Salvador, Nicaragua, Panama, Dominican Republic, Cuba, Haiti, Ecuador, Peru, Chile, Brazil, Venezuela, and Colombia. (CIAT)